Analysis of the refractive status in patients with age-related cataract and shallow anterior chamber after phacoemulsification - Juan Sun (Guoji Yanke Zazhi, 2020)
AIM: To explore the characteristics of refractive changes in patients with age-related cataract and shallow anterior chamber after phacoemulsification. METHODS: A retrospective study was conducted. 96 patients(112 affected eyes)with age-related cataract who were admitted to the hospital between March 2018 and June 2019 were divided into the shallow anterior chamber group(ACD≤2.20mm, 52 patients with 62 affected eyes)and the control group(ACD between 2.21 and 2.90 mm, 44 cases with 50 affected eyes)according to the anterior chamber depth(ACD). All subjects were treated with phacoemulsification. The diopter, ACD and anterior chamber volume(ACV)were measured before surgery, at 1d and 3mo after surgery. Pearson linear correlation analysis was performed to analyze the relationship between the refractive status and anterior chamber parameters in patients with age-related cataract and shallow anterior chamber after phacoemulsification. RESULTS: The diopter error in the shallow anterior chamber group was higher than that in the control group at 3mo after surgery(P<0.001). The variations of ACD and ACV in the shallow anterior chamber group before surgery, at 1d and 3mo after surgery were higher than those in the control group(P<0.001). In the control group, there was no obvious correlation between the diopter error at 1d, 3mo after surgery and preoperative ACD, preoperative ACV, variations of ACD or ACV at different time after surgery(P>0.05). In the shallow anterior chamber group, the diopter error at 3mo after surgery was negatively correlated with preoperative ACD(P<0.05). The diopter error of at 3mo after surgery was positively correlated with variations of ACD at 1d and 3mo after surgery(P<0.05), but there was no obvious correlation with variations of ACV(P>0.05). CONCLUSION: There is hyperopic shift in patients with age-related cataract and shallow anterior chamber after phacoemulsification. The degree of hyperopic shift is negatively correlated with preoperative ACD and positively correlated with postoperative ACD, namely, the smaller the preoperative ACD, the larger the postoperative ACD, the severer hyperopic shift.